2020
DOI: 10.1371/journal.pone.0243884
|View full text |Cite
|
Sign up to set email alerts
|

Self-efficacy and fatigue among non-frontline health care workers during COVID-19 outbreak: A moderated mediation model of posttraumatic stress disorder symptoms and negative coping

Abstract: Purposes Since a considerable number of health care workers (HCWs) were sent to Wuhan to aid COVID-19 control during the epidemic, non-frontline HCWs who stayed in local hospitals had to work overload to provide daily health care services for other health issues, which makes them more vulnerable to experience fatigue. Self-efficacy is suggested as a protective factor for fatigue. Nonetheless, less is known regarding the underlying mechanisms. This research aimed to explore the prevalence of fatigue among non-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
5
29
0
2
Order By: Relevance
“…Burnt out, one of the impacts of this situation may lead to psychological disorders with more prolonged exposure. This finding was supported by a study in Shanghai [ 26 ]. The researchers suggested that after a considerable number of healthcare workers were deployed to Wuhan to control the initial COVID-19 outbreak, non-frontline healthcare providers experienced more fatigue due to the higher workload required compared to the daily healthcare services they generally provided for other health issues.…”
Section: Discussionsupporting
confidence: 76%
“…Burnt out, one of the impacts of this situation may lead to psychological disorders with more prolonged exposure. This finding was supported by a study in Shanghai [ 26 ]. The researchers suggested that after a considerable number of healthcare workers were deployed to Wuhan to control the initial COVID-19 outbreak, non-frontline healthcare providers experienced more fatigue due to the higher workload required compared to the daily healthcare services they generally provided for other health issues.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies involving college students have also identified problem‐focused coping behaviors, including seeking social support, and problem‐solving behaviors as equally vital to increase their adaptability and hardiness against stressful events 50,51 . Further, adequate coping skills have been found to minimize the mental and psychological consequences of traumatic events, emergency and disaster events, and disease outbreaks 22,29,52 . Higher levels of coping skills were found to contribute to a significant reduction in psychological issues (e.g., stress, anxiety, depression) related to the COVID‐19 pandemic among college students in China, 53 the USA, 54 and Switzerland 34 .…”
Section: Discussionmentioning
confidence: 99%
“…[56,57] Various studies also highlight that stressrelated symptoms that may be included in the diagnostic criteria for PTSD are strongly related to somatic symptoms in the COVID-19 era. [58][59][60] On the other hand, the second most significant predictor in the model of this study was found to be the level of PR, which worked as a protective factor for psychosomatic health. In Greece, little evidence supported the link between psychosomatic health and resilience before the COVID-19 outbreak.…”
Section: Comparing the Findings With Previous Studiesmentioning
confidence: 54%